Simulations of Non-Enzymatic Template Directed RNA Replication - Chamanian, Pouyan (My University, 2022)
The universal traits of cellular expression and replication in modern life point to the existence of an ancient RNA world. Leading up to the origin of life, this stage of evolution utilized RNA as the genetic material, and as a catalyst in the form of ribozymes. Although it is expected that a polymerase ribozyme was required for the efficient replication of RNA, it is also likely that the earliest form of replication took place under non-enzymatic conditions. There are several problems with the current scenarios depicting non-enzymatic RNA replication, thus we aim to examine them in more detail using computational models. We first consider the relationship between the thermodynamics of RNA base pairing and non-enzymatic nucleotide addition in an attempt to model the rate of primer extension. Our predicted rates reveal the model parameters to be too simple to produce reliably accurate results. For now, we should simply use available experimental rate data, until we have access to more data and less unknown parameters. Nevertheless, the model indicates that the primer extension rate does depend on thermodynamics of base pairing, and a more accurate model can be of great use when creating realistic complex models of RNA world scenarios. In chapter 3, we investigate non-enzymatic RNA replication under temperature cycling using computer simulations. When starting with a diverse mixture of sequences, partially matching sequences can reanneal in configurations that allow continued strand growth. This is in contrast to the case of having multiple copies of matching sequences, where reannealing occurs quickly upon cooling. We find that, starting with short oligomers, strands can grow over multiple cycles to produce long sequences over 100 nucleotides in length. The small strand extension per cycle does not produce replicates of any one specific sequence. This relates to the work done in chapter 4, where we look for the presence of a virtual circular genome within our simulations. In a virtual circle, short overlapping RNA sequences will make up a mutually catalytic set. Within the diversity of our simulation, virtual circles are rare, and require a specific level of starting mixture diversity along with no input of new sequences. Continued replication of the diverse sequence mixture and emergence of long strands may eventually lead to the creation of rolling circles and ribozymes.
Keywords: RNA world; non-enzymatic; RNA replication; simulations